Preliminary Study: Renewable Bionergy Based On Problem Based Learning as a Recommended Media to Improve Students' Critical Thinking Skills: Penelitian - Eka Sintiya Wati; Eko Hariyono; Azar Zakaria; Hanandita Veda Saphira (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to identify the need for Problem-Based Learning (PBL) based instructional media on the topic of renewable bioenergy and evaluate its effectiveness in enhancing students' critical thinking abilities. Using a descriptive quantitative approach, the study employed test instruments based on Facione’s critical thinking indicators interpretation, analysis, inference, and evaluation and collected data through pretests and posttests administered to 36 students at SMAN 7 Surabaya. The findings revealed an increase in average scores from 2.06 to 3.64 after the learning intervention, with most students reaching the “good” and “very good” performance categories. Properly integrated learning media, including teaching modules, student worksheets (LKPD), PhET virtual simulations, and PowerPoint presentations, proved effective in supporting contextual and impactful PBL implementation. These results underscore the potential of renewable bioenergy themed PBL media as an innovative tool for promoting students’ critical thinking skills while also fostering scientific literacy and environmental awareness.